Effects of a Computerized Training on Attentional Capacity of Young Soccer Players - Reigal, Rafael E.; González-Guirval, Fernando; Morillo-Baro, Juan P.; Morales-Sánchez, Verónica; Juárez-Ruiz de Mier, Rocío; Hernández-Mendo, Antonio (Frontiers in Psychology, 2019)
The purpose of this work was to analyze the effects of a computerized training on attentional capacity in a group of young soccer players. 75 male adolescents from two soccer clubs in the city of Malaga (Spain) and aged between 14 and 18 (15.45 ± 1.43 years), participated in the investigation. A quasi-experimental design was used, and the adolescents were divided into control (n= 38) and experimental (n= 37) groups. The experimental group underwent a computerized training (Rejilla 1.0) of their attention during 9 weeks and 27 sessions. In addition, the D2 attention test was used to analyze the evolution of participants after the intervention program. The results showed positive effects of the computerized intervention program on selective attention, observing changes both in the executions of the software used (p< .001, Cohen’s d= 1.58, 95% CI [1.06, 2.11]) and in the main measures of the D2 test, total effectiveness (p< .001, Cohen’s d= .62, 95% CI [.15, 1.08]) and concentration (p< .01, Cohen’s d= .48, 95% CI [.02, .94]).